Demand and influencing factors of “Internet + Traditional Chinese Medicine” home nursing service for older adult patients with chronic diseases: a mixed research perspective - Wang, Xinghuan; Chen, Jinyan; Feng, Meiqin; Zhuang, Miaoqing; Wang, Jiayi; Zhang, Luyu; Liu, Yue; Chen, Hongfang (Frontiers in Public Health, 2023)
Background In the context of global aging, the characteristics of chronic diseases seriously affect the quality of life of older adults. It is urgent to carry out continuous nursing basis for older adult patients with chronic diseases. In view of the remarkable efficacy of Chinese medicine in the treatment of chronic diseases, this study may help to understand the demand for “Internet + Chinese medicine” home care service and its influencing factors of older adult chronic disease patients, and to provide a reference basis for improving the quality of life of the older adult chronic disease population. Methods This is a mixed study. The quantitative study adopted the convenience sampling method, and a total of 308 patients in a third-grade hospital in Shaanxi Province were investigated by general data questionnaire, traditional Chinese medicine service demand questionnaire, traditional Chinese medicine knowledge questionnaire, older adult Chinese medicine attitude questionnaire, and home care demand questionnaire from March to April 2022. In the qualitative study, semi-structured interviews were adopted, and patients were interviewed until the content was saturated. Colaizzi analysis method was used to analyze and summarize the topic of the interview data. Results 308 valid questionnaires were collected, and the patients scored (58.42 ± 17.16) on the demand for TCM nursing services, (59.86 ± 11.54) on the knowledge of TCM, (73.03 ± 9.11) on the attitude toward TCM, and (136.84 ± 46.39) on the demand for home care. The results of multiple linear regression showed that learning about the nursing service pathway, knowledge of general knowledge of Chinese medicine, and attitude toward Chinese medicine among the older adult and home care demand were the influencing factors of the demand for Chinese medicine nursing services for older adult patients with chronic diseases (p < 0.05). The results of the in-depth interviews were summarized into three themes: facilitating factor, hindering factor, and the “Internet + Chinese medicine” multiple needs of home care. Conclusion Older adult patients with chronic diseases have a high intention of home care demand and they are affected by multiple factors. Consequently, the actual demand situation of older adult patients with chronic diseases should be used as a guide to provide directed and diversified Chinese medicine home care services to meet the individualized needs of the older adult.